Safety, Tolerance, and Enhanced Efficacy of a Bioavailable Formulation of Curcumin With Fenugreek Dietary Fiber on Occupational Stress: A Randomized, Double-Blind, Placebo-Controlled Pilot Study. Issue 3 (June 2016) - Pandaran Sudheeran, Subash; Jacob, Della; Natinga Mulakal, Johannah; Gopinathan Nair, Gopakumar; Maliakel, Abhilash; Maliakel, Balu; Kuttan, Ramadasan; IM, Krishnakumar
Abstract : Abstract: Drug delivery systems capable of delivering free (unconjugated) curcuminoids is of great therapeutic significance, since the absorption of bioactive and permeable form plays a key factor in mediating the efficacy of a substance which undergoes rapid biotransformation. Considering the recent understanding on the relatively high bioactivities and blood-brain–barrier permeability of free curcuminoids over their conjugated metabolites, the present human study investigated the safety, antioxidant efficacy, and bioavailability of CurQfen (curcumagalactomannoside [CGM]), a food-grade formulation of natural curcumin with fenugreek dietary fiber that has shown to possess improved blood-brain–barrier permeability and tissue distribution in rats. In this randomized double-blinded and placebo-controlled trial, 60 subjects experiencing occupational stress-related anxiety and fatigue were randomized to receive CGM, standard curcumin, and placebo for 30 days (500 mg twice daily). The study demonstrated the safety, tolerance, and enhanced efficacy of CGM in comparison with unformulated standard curcumin. A significant improvement in the quality of life ( P < 0.05) with considerable reduction in stress ( P < 0.001), anxiety ( P < 0.001), and fatigue ( P < 0.001) was observed among CGM-treated subjects as compared with the standard curcumin group, when monitored by SF-36, Perceived Stress Scale with 14 items, and Beck Anxiety Inventory scores. Improvement in the quality of life was further correlated with the significant enhancement in endogenous antioxidant markers ( P < 0.01) and reduction in lipid peroxidation ( P < 0.001). Further comparison of the free curcuminoids bioavailability after a single-dose (500 mg once per day) and repeated-dose (500 mg twice daily for 30 days) oral administration revealed enhanced absorption and improved pharmacokinetics of CGM upon both single- (30.7-fold) and repeated-dose (39.1-fold) administrations. Abstract : Supplemental digital content is available in the text.